A Provider-Based Survey To Assess Bereavement Care Knowledge, Attitudes, and Practices in Pediatric Oncologists - Jensen, Jasmin (J Palliat Med, 2017)
Background: Bereavement support is a core tenet of palliative care that may prove difficult for clinicians as it is time-consuming, emotionally charged, and not emphasized in pediatrics training. This project is intended to describe the opinions, knowledge, and practice of bereavement care among pediatric oncologists to identify gaps in clinical care. Procedures: An internet-based survey instrument was pilot tested, refined, and distributed to pediatric oncologists in the United States. Statistical analysis was performed using SAS 9.2. Results: Electronic surveys were distributed to 2,061 pediatric oncologists and 522 surveys (25%) were fully completed. Participants were asked how likely they are to engage in particular bereavement activities (phone calls, condolence cards, memorial services, family meetings, or referrals for counseling) following the death of a pediatric cancer patient. Eighty-two percent of participants, at least, sometimes engage in at least one of these activities. Being female, an attending physician, and increased time in clinical practice were predictive of active participation in bereavement care. Nearly all participants (96%) believe that bereavement care is part of good clinical care, while 8% indicate that bereavement support is not their responsibility. Lack of time and resources were the biggest barriers to providing bereavement support. Conclusions: The majority of pediatric oncologists engage in clinical practices to support bereaved families. Lack of time and physical resources pose significant barriers to clinician's efforts. Additional supports should be explored to increase pediatric oncology physician uptake of bereavement care practices.